African Migrant Traders' Experiences in Johannesburg Inner City: Towards the Migrant Calculated Risk and Adaptation Framework. Issue 1 (2nd January 2018) - Moyo, Inocent; Gumbo, Trynos; Nicolau, Melanie D.
ABSTRACT: Globally, migrants face numerous socio-economic and institutional impediments that hinder their participation in the labour market of host cities and/or countries. This motivates them to join the informal economic sector to make a living. Applying the concept of tactical cosmopolitanism to understand the social and economic agency of African migrants, this article reports on an explorative analysis of the experiences of informal African migrant street traders (African migrant traders) operating in Johannesburg inner city, Gauteng, South Africa. The study revealed that African migrant traders left their countries of origin to secure better opportunities and to escape hostile conditions in their home countries. Despite the host city turning out to be more hostile and xenophobic, making life and finding formal employment opportunities more challenging, the thought of the more difficult life conditions in their home countries has led them to trading on the streets. Given the risks and challenges, including hostile and xenophobic situations that African migrant traders face in Johannesburg inner city, they have adopted dynamic and agentive strategies to survive and continue operating their businesses. Such findings pointed towards and assisted in the development of the Migrant Calculated Risk and Adaptation Framework.